Global attractive periodic solutions of neutral-type neural networks with delays in the leakage terms - Shihong Zhu; Bo Du (AIMS Mathematics, 2023)
In this paper, we introduce a class of neutral-type neural networks with delay in the leakage terms. Using coincidence degree theory, Lyapunov functional method and the properties of neutral operator, we establish some new sufficient criteria for the existence and global attractiveness of periodic solutions. Finally, an example demonstrates our findings.